Transmission of Ebola Viruses: What We Know and What We Do Not Know - Osterholm, Michael T.; Moore, Kristine A.; Kelley, Nicholas S.; Brosseau, Lisa M.; Wong, Gary; Murphy, Frederick A.; Peters, Clarence J.; LeDuc, James W.; Russell, Phillip K.; Van Herp, Michel; Kapetshi, Jimmy; Muyembe, Jean-Jacques T.; et al. (mBio, 2015)
Available evidence demonstrates that direct patient contact and contact with infectious body fluids are the primary modes for Ebola virus transmission, but this is based on a limited number of studies. Key areas requiring further study include (i) the role of aerosol transmission (either via large droplets or small particles in the vicinity of source patients), (ii) the role of environmental contamination and fomite transmission, (iii) the degree to which minimally or mildly ill persons transmit infection, (iv) how long clinically relevant infectiousness persists, (v) the role that “superspreading events” may play in driving transmission dynamics, (vi) whether strain differences or repeated serial passage in outbreak settings can impact virus transmission, and (vii) what role sylvatic or domestic animals could play in outbreak propagation, particularly during major epidemics such as the 2013–2015 West Africa situation. In this review, we address what we know and what we do not know about Ebola virus transmission. We also hypothesize that Ebola viruses have the potential to be respiratory pathogens with primary respiratory spread.